An Overview of Selenium Uptake, Metabolism, and Toxicity in Plants - Gupta, Meetu; Gupta, Shikha (Frontiers in Plant Science, 2017)
Selenium (Se) is an essential micronutrient for humans and animals, but lead to toxicity when taken in excessive amounts. Plants are the main source of dietary Se, but essentiality of Se for plants is still controversial. However, Se at low doses protects the plants from variety of abiotic stresses such as cold, drought, desiccation and metal stress. In animals, Se acts as an antioxidant and helps in reproduction, immune responses, thyroid hormone metabolism. Selenium is chemically similar to sulfur, hence taken up inside the plants via sulfur transporters present inside root plasma membrane, metabolized via sulfur assimilatory pathway, and volatilized into atmosphere. Selenium induced oxidative stress, distorted protein structure and function, are the main causes of Se toxicity in plants at high doses. Plants can play vital role in overcoming Se deficiency and Se toxicity in different regions of the world, hence, detailed mechanism of Se metabolism inside the plants is necessary for designing effective Se phytoremediation and biofortification strategies.